Relation between serum quantitative HBsAg, ALT and HBV DNA levels in HBeAg negative chronic HBV infection - Günal, Özgür; Barut, Şener; Etikan, İlker; Duygu, Fazilet; Tuncel, Umut; Sünbül, Mustafa (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: In this study, we aimed to investigate whether quantitative HBsAg and alanine aminotransferase (ALT) levels correlated with Hepatitis B Virus (HBV) DNA levels in patients with HBeAg negative chronic HBV infection. Materials and Methods: Ninetynine patients were divided into two groups; inactive HBsAg carriers (IC) and active carriers (AC) with HBV DNA >2000 IU/mL. These two groups were compared in terms of ALT and HBsAg levels. Quantitative HBsAg measurements were performed with Elecsys HBsAg II Quant assay (Roche Diagnostic) Results: Mean age of patients was 43.11±14.79 years. HBsAg and ALT values of IC and AC patients were 2.47±1.35 log10 IU/mL, 3.59±0.97log10 IU/mL (p=0.0001), and 25.94±13.06 IU/mL, 55.54±82.38 IU/mL (p=0.015), respectively and the difference was significant. When ROC analysis was performed to determine the most appropriate quantitative HBsAg value to define inactive carrier patients, the area under the ROC curve for HBsAg was 0.738 (95% CI:0.637-0.840). A cut-off of 2147 IU/mL revealed sensitivity of 76% and specificity of 70% for diagnosing the IC. Also, a significant correlation was also found between levels of HBV DNA (log) and HBsAg (log) (r: 0.503, p=0.0001). Conclusion: It has been concluded that quantitative measurements of HBsAg could be used to differentiate between IC and AC patients.